ISFT - INTERNATIONAL SCHOOL OF FINANCE TECHNOLOGY AND SCIENCE - Raimjanova Makhbuba Nomanovna (Journals Park Publishing, 2024)
The International School of Financial Technology and Sciences (ISFT) stands as a beacon of innovation in the realm of financial education, blending cutting-edge technology with traditional financial principles. This article delves into ISFT's mission, academic programs, research initiatives, and impact on the global financial landscape. By fostering a dynamic learning environment and promoting interdisciplinary collaboration, ISFT is shaping the future of financial education and technology.
Keywords: ISFT, financial education, financial technology, innovation, interdisciplinary collaboration.